Association between Parkinson's disease and risk of colorectal cancer: A systematic review and meta‐analysis - Meng‐Dan Su; Tian‐Hong Wang; Hao‐Wen Zhang; Ke‐Yu Cao; Fei Liu (Ibrain)
Abstract This study aims to investigate the relationship between Parkinson's disease (PD) and colorectal cancer (CRC) risk by a systematic review and meta‐analysis. Using Embase, Pubmed, and Cochrane Library databases, 21 articles reporting clinical data of 1,635,873 PD patients and 10,388,842 healthy individuals were finally included. Based on the results of pooled analysis, we found that PD patients exhibited a decreased risk of CRC (relative risk (RR) = 0.74; 95% confidence interval (CI), 0.68–0.80). In contrast to case‐control (RR = 0.80; 95% CI, 0.64–1) and cohort studies (RR = 0.72; 95% CI, 0.66–0.79), the combined risk of PD patients with CRC in Asian nations (RR = 0.67; 95% CI, 0.58–0.78) was lower than that in Western countries (RR = 0.76; 95% CI, 0.70–0.82). In comparison to rectal cancer (RR = 0.82; 95% CI, 0.69–0.97), PD patients exhibited a lower combined risk of colon cancer (RR = 0.76; 95% CI, 0.67–0.86). Furthermore, the combined CRC risks for patients in studies published before 2010 and after 2010 were 0.76 (RR = 0.76; 95% CI, 0.66–0.88) and 0.74 (RR = 0.74; 95% CI, 0.68–0.80), respectively. These findings indicate that patients with PD had a reduced risk of CRC. Future studies are merited in exploring pathological molecular linkages or underlying mechanisms of inverse association between CRC and PD.